The performance of initial public offerings (IPOs) of Sarawak listed companies - Nasriman, bin Abdul Rahman (Universiti Malaysia Sarawak, (UNIMAS), 2002)
This paper investigates the IPO performance of Sarawak based listed firms. Using a sample of 22 firms, the findings suggest that the IPO performance shows the same pattern as previous studies. These IPOs are relatively underpriced, possibly due to investors interest as evidence by the average first day premium fetched of approximately 83.9%.